The Correlation of Vocabulary and Sentence Mastery towards Students’ Writing Ability on Description Text - Oktaviani, Ria; Nurchurifiani, Eva; Hastuti, Hastuti (IJLHE: International Journal of Language, Humanities, and Education, 2021)
The problem raised in this study is the relationship between vocabulary and sentence mastery and the ability to compose descriptions. This research was conducted because of the reality in the field that the ability to compose descriptions and mastery of vocabulary, as well as sentences that need to be developed. This study aims to describe the relationship between vocabulary and sentence mastery and the ability to compose a description of the seventh grade students of SMPN 26 Bandar Lampung. The techniques used in collecting research data are questionnaires, tests, and observations. Research data analysis techniques include requirements analysis test, statistical analysis, and research hypothesis testing techniques. Based on the results of the study, it can be concluded that, (1) there is a positive and significant relationship between sentence structure and the ability to compose descriptions, indicated by a correlation coefficient of 0.766 and a coefficient of determination (R2) of 0.587 or 58.7%, (2) there is a relationship a positive and significant relationship between vocabulary mastery and the ability to compose descriptions indicated by a correlation coefficient of 0.662 and a coefficient of determination (R2) of 0.438 or 43.8%, (3) there is a positive and significant relationship between vocabulary mastery and sentence structure and ability composing a description shown by the correlation coefficient of 0.804 and the coefficient of determination (R2) of 0.646 or 64.6%.